Academic librarians’ roles and competencies in research partnership: A qualitative study - Rabasa, Talatu Adamu; A.Abrizah, (Malaysian Journal of Library and Information Science, 2022)
In the past decades, academic librarianship has been preoccupied with changes that include academic librarians as research partners due to the changing landscape in scholarly communication services, evolving technologies, and institutional missions. Thus, the idea of academic librarians being a partner in research rather than mere research supporters is a new development in academic librarianship that requires attention, especially on what academic librarians can do to partner with the research community successfully. Therefore, this study employed a qualitative approach to explore academic librarians’ roles as research partners and the competencies required for better collaborations. Data were generated through face-to-face interviews with 14 academic librarians purposively sampled from a major research university in Nigeria. Ten themes emerged from the findings regarding academic librarians' role as research partners. These include information discovery and provision, information use and evaluation; grants application; articulation of research topic; literature and reference management; research data management, systematic review, authoring a manuscript, scholarly publishing, and research dissemination. Similarly, eleven themes emerged as the competencies required to be analysed under the dimensions of knowledge, skill, and attitude. These include research methodology and research data management as the knowledge needed in a research partnership. While digital scholarship, systematic review, reference / citation management, data curation and preservation, bibliometrics/information evaluation and communication emerged as the skills required for the effective discharge of their responsibilities. Professionalism, patience, and cordiality were found to be the attitude required. This paper is limited to providing academic librarians with the necessary authority to enhance their performance in a research partnership, and offering them the approach to guide their practice in a research partnership. Thus, the study recommended, among others, the need for enlightenment programmes and activities for academic librarians that cut across training, workshops, and organising conferences in research areas in enhancing their service performance to ensure successful research partnerships.